Diagnostic value of pipelle endometrial sampling in comparison with dilatation and curettage among patients with abnormal uterine bleeding - A.S., Alliratnam; S., , Senthil Priya; R., Shankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Dilatation and curettage (D&C) is the gold standard for endometrial sampling, but 60% of cases less than half of the uterine cavity is curetted, with the added risk of general anesthesia, infection and perforation, whereas pipelle does not require a syringe or pump nor require general anesthesia or cervical dilatation and permits almost painless endometrial sampling. The aim and objectives of the study was to determine the reliability of pipelle device in acquiring an adequate & representative endometrial sample comparing to D&C and to comparing the result of histopathological diagnosis of pipelle sampling with D&C. Methods: A cross-sectional study was done at Vinayaka Missions Medical College Salem between September 2014-August 2015. 100 cases of AUB attending the outpatient clinic in the department of obstetrics & gynecology were included in the study. Endometrial sampling with pipelle device was performed in 100 patients followed by formal D&C. Results: For obtaining the endometrial sample the sensitivity of pipelle sampling was 97% and the specificity was 100% when compared with D&C sampling. The diagnosis made by the HPE report by the sample obtained from pipelle sample had shown a very high sensitivity, specificity, positive predictive value and negative predictive value, except for the diagnosis of endometrial polyp which the pipelle sample was not able to detect. Conclusions: The pipelle is a safe technique of endometrial biopsy for getting an adequate endometrial sample for histopathology, with high sensitivity and specificity for endometrial pathologies and endometrial carcinoma.